Variable Ventilation Is Equally Effective as Conventional Pressure Control Ventilation for Optimizing Lung Function in a Rabbit Model of ARDS - Fodor, Gergely H.; Bayat, Sam; Albu, Gergely; Lin, Na; Baudat, Aurélie; Danis, Judit; Peták, Ferenc; Habre, Walid (Frontiers in Physiology, 2019)
Background: Introducing mathematically derived variability (MVV) into the otherwise monotonous conventional mechanical ventilation has been suggested to improve lung recruitment and gas exchange. Although the application of a ventilation pattern based on variations in physiological breathing (PVV) is beneficial for healthy lungs, its value in the presence of acute respiratory distress syndrome (ARDS) has not been characterized. We therefore aimed at comparing conventional pressure-controlled ventilation with (PCS) or without regular sighs (PCV) to MVV and PVV at two levels of positive end-expiratory pressure (PEEP) in a model of severe ARDS. Methods: Anaesthetised rabbits (n=54) were mechanically ventilated and severe ARDS (PaO2/FiO2≤150 mmHg) was induced by combining whole lung lavage, i.v. endotoxin and injurious ventilation. Rabbits were then randomly assigned to be ventilated with PVV, MVV, PCV or PCS for 5 hours while maintaining either 6 or 9 cmH2O PEEP. Ventilation parameters, blood gas indices and respiratory mechanics (tissue damping, G, and elastance, H) were recorded hourly. Serum cytokine levels were assessed with ELISA and lung histology was analysed. Results: Although no progression of lung injury was observed after 5 hours of ventilation at PEEP 6 cmH2O with PVV and PCV, values for G (58.8±71.1[half-width of 95% CI]% and 40.8±39.0%, respectively), H (54.5±57.2%, 50.7±28.3%), partial pressure of carbon-dioxide (PaCO2, 43.9±23.8%, 46.2±35.4%) and pH ( 4.6±3.3%, 4.6±2.2%) worsened with PCS and MVV. Regardless of ventilation pattern, application of a higher PEEP improved lung function and precluded progression of lung injury and inflammation. Histology lung injury scores were elevated in all groups with no difference between groups at either PEEP level. Conclusions: At moderate PEEP, variable ventilation based on a pre-recorded physiological breathing pattern protected against progression of lung injury equally to the conventional pressure-controlled mode, whereas mathematical variability or application of regular sighs caused worsening in lung mechanics. This outcome may be related to the excessive increases in peak inspiratory pressure with the latter ventilation modes. However, a greater benefit on respiratory mechanics and gas exchange could be obtained by elevating PEEP, compared to the ventilation mode in severe ARDS.